Motor coordination during the underwater undulatory swimming phase of the start for high level swimmers - Elipot, M.; Houel, N.; Hellard, P.; Dietrich, G. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: In swimming event, start is determinant to achieve a good race performance. During the underwater undulatory swimming phase, swimmers have to find the optimal leg motor coordination to produce the highest propulsive forces without increasing the hydrodynamic resistances. The aim of this study is to determine the motor coordination that high level swimmers are able to produce during the underwater undulatory swimming phase of the start. METHODS: 12 high level male swimmers participated in this study. Swimmers were asked to performe the most efficient grab start. Swimmers were filmed during the whole underwater phase of the start by 4 mini-DV camcorders. Nine anatomical landmarks were identified on the swimmer`s body. To minimise the error during the digitising process, both sides of the swimmers were supposed to be symmetric. Landmarks space coordinates have been calculated using a modified 2D DLT technique (inspired from Drenk et al., 1999). Space reconstruction accuracy was 6.2 mm. Ankle, knee and hip angles and positions were calculated. Motor coordinations and synergies were identified by computing cross correlation functions. RESULTS: Results show significant cross correlation between: the hip angle and the ankle angle, the hip angle and the trunk angle, the hip angle and the thigh angle of attack, the knee angle and the thigh angle of attack, the knee depth and the thigh angle of attack, the knee depth and the hip angle, the knee depth and the knee angle, the hip angle and the leg angle attack, the knee angle and the leg angle attack, the ankle depth and the hip angle, the ankle depth and the knee angle, the toes depth and the hip angle, the toes depth and the knee angle, the toes depth and ankle angle. DISCUSSION: During the underwater undutory swimming, swimmers have to find the optimal leg amplitude. It seems that high level swimmers control leg amplitude thanks to a strong joint synergy between the hip action and the ankle action. Knee action is also important but seems to have an independent effect on leg amplitude.